IMPLEMENTASI MODEL COOPERATIVE SCRIPT BERBANTUAN CERITA BERGAMBAR DALAM MEMBACA INTENSIF PESERTA DIDIK SEKOLAH DASAR - Asni Deselia Khairunnisa; Mahmudah; Ella; Muna Salma (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
Intensive reading skills are an important ability that elementary school students need to master in order to understand reading material in depth. However, observations show that students’ intensive reading skills are still low, especially in determining main ideas, understanding detailed information, and answering questions based on the text. This study aims to improve intensive reading skills through the application of the Cooperative Script model assisted by picture story media. The research used a qualitative approach with a Classroom Action Research (CAR) design, which was carried out collaboratively with 21 fourth-grade students at SDN Gambut 10. The research was conducted in two cycles, which included the planning, implementation, observation, and reflection stages. Data were collected through intensive reading tests and observation sheets of teacher and student activities. The results showed an increase in teacher activity, student activity, and students’ intensive reading skills. Classical mastery increased from 43% in cycle I to 86% in cycle II. Thus, the Cooperative Script model assisted by picture stories proved to be effective in improving the intensive reading skills of elementary school students. Keywords: Cooperative Script, Illustrated Story, Intensive Reading